Research trends on the gut microbiota in endocrine metabolism: a thematic and bibliometric analysis - Doğan, Durmus; Çelik, Taylan (Frontiers in Cellular and Infection Microbiology, 2024)
Background Gut microbiota studies in the field of endocrinology metabolism have attracted increasing attention in recent years. To comprehensively assess the evolving landscape of this research field, we conducted a thorough bibliometric analysis of gut microbiota studies in endocrinology metabolism indexed in the Web of Science database. Methods We collected and analyzed 3,339 original research articles and reviews published from 1972 to 2023. Using various bibliometric indicators, we investigated publication trends, country contributions, international collaborations, prolific authors, top journals, and influential articles. Results Our analysis revealed a significant upsurge in publications after 2010, indicating a growing scientific interest in microbiota and endocrinology metabolism. Keyword and thematic analyses have identified gut microbiota, obesity, diabetes, and inflammation as core research themes. Additionally, the roles of probiotics and prebiotics are increasingly researched for their therapeutic effects in shaping the microbiota. Conclusion This study reveals that research in endocrinology metabolism is increasingly decoding the connection between gut microbiota and diseases. There’s also a growing focus on microbiota manipulation, which points to a shift towards personalized medicine. Future research should focus on integrating these findings into clinical practice, moving from lab-based studies to real-world patient care.